A simplified coupling model of carbonation and chloride ingress based on Stefan-like condition. Issue 7 (19th May 2022) - Zhu, Xingji; Dai, Xuerui; Liu, Lu; Bian, Wenfeng; Xu, Longjun; Meng, Zhaozheng
Abstract: Practical observations demonstrate that the corrosion deterioration of numerous reinforced concrete structures is due to the combination of carbonation and chloride ingress. However, the comprehensive combined model developed directly based on the coupling mechanism of them is very complicated. This article presents a simplified model to describe the transport of chloride ions with carbonation by introducing the Stefan condition, which is mainly used for the mathematical modelling of boundary movement caused by phase transformation in thermodynamics. Meanwhile, the influence function of carbonation on the diffusion coefficient of chloride ion is also re-discussed. An empirical formula is fitted directly according to the mix proportions of concrete, which can greatly reduce the computational cost. Then, an intuitively expressed formula of chloride concentration distribution under the influence of carbonation can be solved. Ultimately, its prediction accuracy is verified by two experiments.